Risk evaluation and interventional planning for cerebral aneurysms: computational models for growth, coiling and thrombosis - Ventikos, Y; Bowker, T; Watton, P; Kakalis, N; Byrne, J (2009)
The clinical treatment of cerebral aneurysms, from detection to post-intervention follow-up care, poses a series of challenges, both clinical and technical. The introduction of computational simulation techniques, in all stages of the procedure, allows for, or promises to provide, patient-specific risk evaluation, rationalisation and optimisation of surgical or interventional planning and a priori evaluation of treatment efficacy and long-term outcome. In this article, we present techniques that allow for the simulation of growth of cerebral aneurysms, based on detailed vascular wall remodelling techniques. Moreover, we demonstrate that computational techniques allow the preinterventional evaluation of the effectiveness of detachable coil implantation. Finally, appropriate coupling of the haemodynamics of flow with thrombosis models allows for the prediction of the growth of clot; of great importance both of the eventual healing of the lesion in case of endovascular coil treatment for cerebral aneurysms but also as an indicator of the spontaneous formation of microembolic clots. © 2009 Taylor and Francis.